Media Pembelajaran Untuk ABK Dengan Model Adaptasi Kurikulum Merdeka Pada Mata Pelajaran Bahasa Indonesia - Opi Andriani; Antika Saputri; Silvi Nuraini (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
The aim of this research is to provide innovation related to learning media for crew members with an independent curriculum adaptation model for Indonesian language subjects, especially learning media for children with visual impairments or who are blind. The method used in this research is a literature review study or literature review. Literature study is a research design used to collect data sources related to a topic found in the field. Data collection for literature studies was carried out using the Google Scholar search tool. The screening results that were appropriate and needed were 3 National Journal articles based on the articles found and analyzed. The results of this research were that a suitable learning media for improving the reading skills of blind students was found to be using audio media in the form of voice recordings.